Fahrenheit 451 - Bradbury, Ray, 1920-2012 (Simon & Schuster, 2012)
In a society in which books are outlawed, Montag, a regimented fireman in charge of burning the forbidden volumes, meets a revolutionary school teacher who dares to read. Suddenly he finds himself a hunted fugitive, forced to choose not only between two women, but between personal safety and intellectual freedom.